2018
DOI: 10.1186/s12887-018-1176-x
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological profile and antibiotic susceptibility of neonatal sepsis in neonatal intensive care unit of a tertiary hospital in Nepal

Abstract: BackgroundNeonatal sepsis, one of the leading causes of mortality in neonatal intensive care units (NICU) of developing countries like Nepal, is often not extensively studied. In order to decrease the morbidity and mortality associated with neonatal sepsis, neonatologists should have a keen knowledge of the existing bacteriological flora and their antibiotic susceptibility pattern. In this study, we aim to determine the bacteriological profile and antibiotic susceptibility pattern of culture positive neonatal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

30
95
8
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(143 citation statements)
references
References 20 publications
30
95
8
10
Order By: Relevance
“…7 The morbidity and mortality may be caused by ineffective antibiotics to multidrug-resistant bacteria or a weak host defense mechanisms in preterm infants. [8][9][10] Adjuvant therapies may be increasingly important to increase the efficacy of antimicrobial agents and overcome excessive or uncontrolled inflammatory response in sepsis. [11][12][13] Redox-active agents (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…7 The morbidity and mortality may be caused by ineffective antibiotics to multidrug-resistant bacteria or a weak host defense mechanisms in preterm infants. [8][9][10] Adjuvant therapies may be increasingly important to increase the efficacy of antimicrobial agents and overcome excessive or uncontrolled inflammatory response in sepsis. [11][12][13] Redox-active agents (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial pathogens such as Klebsiella pneumoniae, Staphylococcus aureus, and coagulase-negative Staphylococcus are the most common causes of neonatal sepsis in developing countries [9]. These organisms are highly resistant to commonly used antibiotics, which makes them challenging to treat [10][11][12]. Moreover, early diagnosis and treatment of newborns with infection are unsatisfactory in resource-poor settings, which contributes to the high neonatal mortality due to sepsis [13].…”
Section: Introductionmentioning
confidence: 99%
“…Gram positive isolates were most sensitive to Vancomycin (100%) while the gram negative isolates were most sensitive to Amikacin.100% sensitivity of CONS to Vancomycin was seen in a recent study from Nepal and from India. 7,16 High sensitivity of Gram negative isolates to Amikacin was also seen in the studies in Cameroon but some studies from India showed only 50% sensitivity. 5,7 Resistance to Crystalline Penicillin, Ampicillin and 3 rd generation cephalosporins was high.…”
Section: Discussionmentioning
confidence: 79%